ANALYSIS OF FREE AND BOUND MORPHEME IN LYRICS OF ED SHEERAN SONG PERFECT - Atigo Alam Chayo; Hanif Maulaniam Sholah (LPPM STAI Muhammadiyah Probolinggo, 2025)
Language can be a tool to communicate with each other in life, language can make individuals relate to each other. The objective of this research is to find out free morpheme and bound morpheme in the